New exact solutions for nonlinear Atangana conformable Boussinesq-like equations by new Kudryashov method - Mirhosseini-Alizamini, Seyed Mehdi; Ullah, Najib; Sabi'u, Jamilu; Rezazadeh, Hadi; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2021)
In this work, we investigate a new Kudryashov method (NKM) to find the exact and some new solutions of four different types of nonlinear Atangana conformable Boussinesq-like equations (NLACBEs). This is an appropriate algorithm for finding the exact solutions and also working for different types of nonlinear confirmable differential equations. In coastal and ocean engineering, some physical phenomenon is based on the exact solutions of the NLACBEs.
Keywords: New Kudryashov method; Boussinesq-like equations; nonlinear Atangana conformable derivatives; exact solutions